Pengaruh Pengenalan Lapangan Persekolahan (PLP), Penguasaan Teknologi Informasi, dan Penguasaan Materi Akuntansi Terhadap Kesiapan Mahasiswa Menjadi Guru Akuntansi Di Era Revolusi Industri 4.0 - Laili Nur Umaroh; Moh Danang Bahtiar (Jurnal Pendidikan Akuntansi (JPAK), 2022)
Readiness to become a teacher in the 4.0 era can grow from various factors, including Introduction to School Fields (PLP), Mastery of Information Technology, and Mastery of Materials. The purpose of this study was to determine the effect of PLP, Mastery of Information Technology, and Mastery of Accounting Materials on Students' Readiness to Become Accounting Teachers in the Era of the Industrial Revolution 4.0. This research is included in the type of quantitative research. The population of this study were students of the 2018 State University of Surabaya Accounting Education Study Program who had participated in PLP II as many as 40 students using the saturated sampling technique. Data collection techniques using a questionnaire questionnaire. The data analysis method used multiple linear regression. The results of the research that have been carried out prove that the Introduction to School Fields (PLP) has a positive and significant effect on student readiness to become accounting teachers in the era of the industrial revolution 4.0, while Mastery of Information Technology and accounting materials has no effect on student readiness to become accounting teachers in the era of the industrial revolution 4.0. Simultaneously the variables of PLP, Mastery of Technology, Mastery of Materials simultaneously affect Students' Readiness to Become Accounting Teachers in Era 4.0.